'Giddy Girls', 'Scandalous Statements' and a 'Burst Bubble': the war babies panic of 1914–1915. Issue 4 (7th June 2018) - Lee, Catherine
ABSTRACT: During a few short months following the outbreak of war in 1914, Britain's press was rife with reports of what was heralded as a new 'social problem'. The alleged impending birth of thousands of 'war babies' to unmarried young women and girls, said to have been fathered by men recently departed for the Western Front, was widely discussed but ultimately proved to be largely fallacious. This article examines the extraordinary 'war babies' episode through the lens of the moral panic, focusing on the impact of exceptional wartime circumstances upon the shifting and conflicting sets of gendered, moral values and attitudes of the period.